2019
DOI: 10.1016/j.cell.2019.05.028
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule Targeting Mutagenic Translesion Synthesis Improves Chemotherapy

Abstract: Highlights d Discovery of JH-RE-06, a compound disrupting REV1-POL zmediated mutagenic TLS d JH-RE-06 induces REV1 dimerization to block the REV1-REV7 interaction d JH-RE-06 sensitizes tumors to cisplatin and reduces mutagenesis in vitro d JH-RE-06 suppresses tumor progression in mice and prolongs animal survival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
140
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 38 publications
1
140
0
Order By: Relevance
“…A potential approach, suggested by experiments in laboratory settings, has been to disrupt pol ζ function to enhance chemotherapeutic effectiveness [33][34][35]. For example, an inhibitor that impairs the interaction of pol ζ with the master regulator REV1 has been developed that sensitizes cancer cells and xenograft tumors to cisplatin treatment [36]. Our work suggests that such inhibitors might also induce an interferon response.…”
Section: An Innate Immune Response Cause By Loss Of Pol ζ Functionmentioning
confidence: 88%
“…A potential approach, suggested by experiments in laboratory settings, has been to disrupt pol ζ function to enhance chemotherapeutic effectiveness [33][34][35]. For example, an inhibitor that impairs the interaction of pol ζ with the master regulator REV1 has been developed that sensitizes cancer cells and xenograft tumors to cisplatin treatment [36]. Our work suggests that such inhibitors might also induce an interferon response.…”
Section: An Innate Immune Response Cause By Loss Of Pol ζ Functionmentioning
confidence: 88%
“…Though this damage tolerance pathway benefits the cell by relieving stalled replication, unregulated TLS activity can detrimentally contribute to mutagenesis and resistance to DNAdamaging cancer therapies. Recent advances have addressed these drawbacks through identification of small molecule inhibitors which target Pol-Pol interactions and/or disrupt mutagenic TLS activity, supplementing the effectiveness of current chemotherapeutic drugs (62)(63)(64)(65)(66)(67)(68). These studies provide a promising new approach for mitigating the role of TLS in chemoresistance and provide an exciting incentive for furthering our understanding of the kinetic and structural foundations of TLS.…”
Section: Discussionmentioning
confidence: 99%
“…By targeting the genetic differences of cancer cells, several molecule-targeting drugs, such as Afatinib and Gefitinib, had been approved by U.S. FDA and shown their promising therapeutic activity against various cancers (Cataldo et al, 2011;Hirsch and Bunn, 2012). However, the therapeutic strategies of "one drug-hits-one target-treats-one disease" still face significant challenges as the drug resistance (To et al, 2019;Wojtaszek et al, 2019). Recent studies suggested that targeting the multiple targets might be a practicable approach to ameliorate the therapeutic activity and selectivity, meanwhile preventing the drug resistance (To et al, 2019).…”
Section: Introductionmentioning
confidence: 99%